2022
DOI: 10.1111/eos.12847
|View full text |Cite
|
Sign up to set email alerts
|

Pathways in the association between added sugar consumption, obesity in mother‐child dyads, and chronic oral disease burden in early childhood

Abstract: In this study, we modeled the pathways in the association of socioeconomic status, frequency of added sugar consumption, and obesity in mother-child dyads with chronic oral disease burden in early childhood using structural equation modeling.A population-based study was conducted on preschoolers from public daycare centers in São Luís, Brazil (n = 674) and their mothers. Chronic oral disease burden in early childhood was a latent variable, representing the shared variance of the following indicators: visible p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…The progression of caries lesions is higher during the first and second decades of life (Kassebaum et al, 2015) when the periodontal tissues experience early signs of breakdown (López et al, 2009). These findings corroborate previous results showing caries correlated with inflammatory periodontal indicators in children and the young (Araújo et al, 2022; Carmo et al, 2018), preceding periodontal destruction (Leite et al, 2017). Our observations in Brazilian and Chilean adolescents showed a higher correlation between caries, pulpal involvement, and PPD ≥4 mm (Carmo et al, 2018; Nascimento et al, 2018), suggesting the combined onset and progression of caries and periodontitis early in life.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The progression of caries lesions is higher during the first and second decades of life (Kassebaum et al, 2015) when the periodontal tissues experience early signs of breakdown (López et al, 2009). These findings corroborate previous results showing caries correlated with inflammatory periodontal indicators in children and the young (Araújo et al, 2022; Carmo et al, 2018), preceding periodontal destruction (Leite et al, 2017). Our observations in Brazilian and Chilean adolescents showed a higher correlation between caries, pulpal involvement, and PPD ≥4 mm (Carmo et al, 2018; Nascimento et al, 2018), suggesting the combined onset and progression of caries and periodontitis early in life.…”
Section: Discussionsupporting
confidence: 92%
“…This construct encompasses a multidimensional variable based on pocket depth ≥4 mm, bleeding on probing (BoP), DMFT index, and untreated caries (Carmo et al, 2018). A similar construct, comprising the indicators of biofilm, caries, and gingivitis, was also observed among 3-5-year-old Brazilian children, indicating that oral conditions cluster early in life (Araújo et al, 2022). Finally, among young adults, Leite et al (2017) identified the number of decayed teeth as a predictor of periodontitis (Leite et al, 2017); that was also the case for Chilean and Finnish adults (Mattila et al, 2010;Strauss et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Chronic Oral Disease Burden comprised a good construct, with indicators of caries and periodontal disease significantly correlated with each other. These data are consistent with our previous findings in children and adolescents, which supported the association between a high frequency of sugar consumption and a heavy burden of oral disease (Araújo et al, 2022; Carmo et al, 2018). In this study, we expanded the knowledge on this topic by using a six times larger sample to test the intake limits of added sugars according to international guidelines for future NCD prevention.…”
Section: Discussionsupporting
confidence: 93%
“…The common risk factors shared by caries and periodontitis prompted us to propose the Chronic Oral Disease Burden , an epidemiologic manifestation analyzed as a latent variable composed of indicators of both diseases (Araújo et al, 2022; Carmo et al, 2018). Using such an approach, we could identify that a high sugar consumption frequency was associated with oral disease burden even from early childhood (Araújo et al, 2022; Carmo et al, 2018). Despite the role of sugar, the effect of the consumption limits recommended by the WHO and the AHA was not assessed in caries and periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%